Aesthetics and consumption - Joy, Annamma (Henry Stewart Talks, 2013)
Aesthetics and consumption, Embodied cognition, Embodied emotion, Sensory experiences and processes, Imagination, Art and art market, Museums and experiencing art, Luxury brands, Haute couture and high fashion brands, Experiential marketing, Metaphor and conceptual blending